PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. TUNAS JAYA UTAMA - Rini Astuti; Suhendri (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
This study aims to determine the effect of compensation on the performance of employees of PT. Jaya Jaya Utama. This study aims to determine the effect of motivation on the performance of PT.Tunas Jaya Utama employees. This study has the aim to determine the effect of compensation and motivation on the performance of PT.Tunas Jaya Utama employees. The population of this research is 32 employees of PT. Tunas Jaya Utama. Data collection techniques in this study were interviews, documentary studies and questionnaires, while the data analysis techniques used were the classic assumption test, multiple regression, T test, F test, and the coefficient of determination. There is an effect of compensation and motivation on employee performance at PT. Tunas Jaya Utama where the count is 0.349. The multiple correlation coefficient values ​​together between motivation and workload on performance obtained Rx1x2y = 0.723. This positive value means that if compensation and motivation are increased the performance will increase. From the F test it was obtained 15,853 with sig 0,000 <0,05, indicating that Ho was rejected and Ha was accepted, meaning compensation (X1) and motivation (X2) had a significant effect on performance (Y) at the 0.05 level. The coefficient of determination obtained (R-Square) is 0.522 or 52.20%, indicating that around 52.20% the variable Y can be explained by the compensation variable (X1) and motivation (X2) or practically it can be said that the contribution of compensation (X1) and motivation (X2) on performance (Y) is 52.20%, the rest is influenced by other variables not examined.